Urine as a social signal in the Mozambique tilapia (Oreochromis mossambicus) - Barata, Eduardo N. (2008)
In order to test whether Mozambique tilapia is actively signalling to conspecifics or the olfactory sensitivity evolved as a form of chemical spying, the current study assessed changes in urination rates of both sexes in different social contexts. Male tilapia modulate their rate of urine release depending on the social context. Together with the fact that conspecific urine contains potent odorants, this strongly suggests that the urine is being used as a chemical signal. Furthermore, territorial males may be signalling their status to potential rivals via their urine as well as via changes in coloration and behaviour. In conclusion, males may actively advertise their dominant status via substances released in the urine, whilst females do not actively advertise their reproductive status. The identity, origins and functional roles of the compounds involved remain to be established.